Photoinduced dynamic tailoring of near-field coupled terahertz metasurfaces and its effect on Coulomb parameters - Kumar, Deepak (2022)
In modern day photonic integrated circuitries (ICs), near-field Coulomb interaction plays an important role in the device performances. In fact, harvesting Coulomb effect intelligently can immensely help to realize advanced photonic devices in micro and nano length scales. In this context, electrically coupled terahertz metasurfaces are investigated for weak and strong near field coupling regimes under the influence of variable photo excitations. Our study demonstrates active tuning of metasurface resonances at relatively low pump powers (up to 10 mW (pump fluence of 12.7 µJ/cm2) and 20 mW (pump fluence of 25.4 µJ/cm2) for strong and weak near field coupling regimes, respectively). We attribute photo induced modifications of substrate electronic properties along with modifications of near-field interactions to be responsible for the resonance modulations. Further, we have demonstrated Coulomb effect parameter can be dynamically tunable with variable pump power. Our study reveals that change in Coulomb parameter is more pronounced for weak near field coupling regime (more than 6 times enhancement in Coulomb parameter) in comparison to strong near field coupling regime. In addition, the optical switching of the fundamental resonance is validated utilizing numerically simulated patterns of surface current & electric field. We envisage such active modulation of Coulomb effects in near-field coupled metasurfaces can lead to realize dynamically tunable terahertz metaphotonic devices.